Analyzing the Relationship Between Teacher-Student Interaction and Sports Facilities on Academic Achievement - Harri Romadhona; Zulfairah (Siber International Journal of Sport Education, 2024)
Analyzing the Relationship Between Teacher-Student Interaction and Sports Facilities on Academic Achievement is a literature review article in the field of education. The purpose of this article is to test the hypothesis that positive interactions between teachers and students, as well as adequate sports facilities, contribute to improved student academic achievement. The research sources were drawn from academic online platforms such as Google Scholar, Mendeley, and educational journals. The method used is library research based on open-access e-books and e-journals. The analysis was conducted qualitatively in a descriptive manner. The findings of this article indicate that: (1) Teacher-student interaction affects student academic achievement, and (2) The availability of adequate sports facilities supports student academic achievement.